Cálculo do perfil de temperaturas em uma vareta combustível de reator pwr com seção transversal em formato hemoglobina, por diferenças finitas em estado estacionário - Santos, Beatriz Machado dos (2018)
In previous studies the performances of a solid cylindrical fuel rod and an annular fuel rod were compared; it was been proven that the annular rod can reach a higher nominal power in relation to the solid one. In this work, the distributions and temperature profiles of two hollow nuclear fuel pellets, one annular and the other in the form of a biconcave disc (similar to the cross section of a red blood cell), were compared to analyze the efficiency and safety of both. The finite differences method allowed the evaluation of the steady thermal behavior of these pellets, taking into account the two-border convection and surface conduction. The results show that the profile that presents the maximum temperature of the hollow biconcave disc pellet is lower, about 70oC below, when compared to the temperature profile of the annular pellet, considering the same simulation parameters for both pellets.